Ag7TaSe6: a new noncentrosymmetric selenide with fascinating "three in one" coordination modes and a strong second harmonic generation response. Issue 25 (18th June 2019) - Li, Zhuang; Zhang, Shengzi; Yin, Wenlong; Kang, Kaijin; Guo, Yangwu; Xing, Wenhao; Lin, Zheshuai; Yao, Jiyong; Wu, Yicheng
Abstract : A new noncentrosymmetric selenide exhibits fascinating "three in one" coordination modes and a strong second harmonic generation response. Abstract : A novel noncentrosymmetric selenide Ag7 TaSe6 has been successfully synthesized and fully characterized. It features fascinating "three in one" coordination modes which provide valuable insights for designing novel nonlinear optical crystals. Furthermore, detailed theoretical and experimental investigations illustrate the origin of Ag7 TaSe6 's strong nonlinear optical response.